Activity Test of Suji Leaf Extract (Dracaena angustifolia Roxb.) on in vitro cholesterol lowering - Devina Ingrid Anggraini; Lily Fathrah Nabillah (Jurnal Kimia Sains dan Aplikasi, 2018)
Cholesterol is a natural substance with physical characteristic similar to fat but has a steroidal group. The body requires cholesterol in normal amount; however, it will harm the body in excess amount. High cholesterol levels in the blood are dangerous because of the precipitation of cholesterol and other fatty substances resulting in atherosclerosis. Suji leaf (Dracaena angustifolia Roxb.) used as a natural dye has a high flavonoid content that is inferred to have cholesterol-lowering activity. This study aims to test the in vitro activity of suji leaf (Dracaena angustifolia Roxb.) extract in decreasing cholesterol level with various concentrations and to find the effective concentration (EC50). The method of extraction used was remaceration method with 70% ethanol solvent. Analysis of cholesterol-lowering activity was done by Lieberman-Burchard method by making variation of ethanol extract 400 ppm, 500 ppm, 600 ppm, 700 ppm, and 800 ppm. The results showed the percentage of cholesterol-lowering activity by 33.62%, 36.15%, 46.61%, 56.39% and 64.05% respectively. Value of EC50 activity of suji leaf extract is 632.50 ppm.